METODE PENYULUHAN PERTANIAN DALAM MENINGKATKAN PENGETAHUAN DAN KETERAMPILAN PETANI (STUDI KASUS DI KECAMATAN MAROS BARU KABUPATEN MAROS) - Imran, Andi Nur; Muhanniah, Muhanniah; Widiati Giono, Bibiana Rini (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2019)
Extensionist agents as one of the important spearheads in advancing agriculture in Indonesia. By counseling will provide information, knowledge, and skills to farmers in trying to farm. One of the factors in improving the knowledge and skills of farmers is to provide effective and efficient extension learning method. This study aims 1) Analyze the Method of agricultural Extension in Maros Baru Sub-district Maros Regency 2) Analyze the influence of Agricultural Extensionist Method in improving Farmers Knowledge and Skills in Maros Baru sub-district. This research was conducted for approximately 3 months, starting from May to July 2018, with the research location is in District Maros Baru. The sample in this study is the existing farmers in the District Maros Baru, with the sampling system by proportional sampling. The method of data analysis are: 1) Qualitative Descriptive Analysis and 2) Test t. The result of the research shows that: A) The Agriculture extension which is categorized as very high is Demplot, Anjangsana, Training and Field School, While the Method of learning extension that as high category is Temu wicara and comparative study. B) The overall agriculture extension Methode is influential in increasing the knowledge and skills of farmers.